Literature Review: Warm Compress with Medicine Plants to Reduce Joint Pain in The Elderly - Dwi Widyastuti; Ramdhani Ismahmudi; Burhanto Burhanto; Afina Agma Fazalina; Auliya Fitri; Fathimah Az-Zahra; Putri Puji Astuti (Global Health Science Group, 2021)
Medicinal plants or herbs have been widely used as a companion or substitute for drugs made from chemicals to overcome health problems. The existence of these medicinal plants can prevent the elderly from using chemical painkillers can cause side effects when consumed for a long time. Some medicinal plants such as onions, ginger, lemongrass, and cinnamon have several active compounds that can reduce joint pain experienced by the elderly by giving warm compresses to the inflamed area. Purpose: to provide evidence-based information obtained from the results of a literature review related to the provision of warm compresses made from medicinal plants in the form of onions, ginger, lemongrass, and cinnamon to reduce joint pain in the elderly. Method: this study is to search for data sources for journal articles through the Google Schooler database, Research Gate, Elsevier, Sage, Portal Garuda, Scopus, Knowledge E, Sinta, Litbangkes with a span of 5-10 years, both in Indonesian and English. Results: based on 73 studies, it was found that giving warm compresses made from onions, ginger, lemongrass, and cinnamon can reduce joint pain in the elderly in the range of moderate to mild pain. Conclusion: giving warm compresses made from medicinal plants onion, ginger, lemongrass, and cinnamon can reduce joint pain experienced by the elderly.